Biomechanics of goal-kicking accuracy in Australian football using an inertial measurement system - Blair, S.; Duthie, G.; Robertson, S.; Ball, K. (ISBS Proceedings Archive (Michigan), 2017)
Accurate goal-kicking is important to a team`s success in Australian Football (AF). However, it remains a largely unexplored area in sport biomechanics. This study examined technical aspects of goal-kicking accuracy using an inertial measurement system (IMS). Two junior AF players performed 15x20m goal-kicks in the field. Kinematics were measured using the Xsens MVN link IMS (240Hz). Results showed that both players had greater support leg (p<0.04; d>1.0) and kick leg (d>1.0) knee flexion during accurate goal-kicks. Individual differences were reported for footspeed and shank angular velocities for accurate goal-kicks. These individual differences highlight the need to conduct an individual-based analysis in goal-kicking research.